Increased Endogenous Activity of the Renin-Angiotensin System Reduces Infarct Size in the Rats with Early Angiotensin II-dependent Hypertension which Survive the Acute Ischemia/Reperfusion Injury - Husková, Zuzana; Kikerlová, Soňa; Sadowski, Janusz; Alánová, Petra; Sedláková, Lenka; Papoušek, František; Neckář, Jan (Frontiers in Pharmacology, 2021)
We investigated the role of the interaction between hypertension and the renin-angiotensin system in the pathophysiology of myocardial ischemia/reperfusion injury. We hypothesized that in the early phase of angiotensin II (ANG II)-dependent hypertension with developed left ventricular hypertrophy, cardioprotective mechanism(s) are fully activated. The experiments were performed in transgenic rats with inducible hypertension, noninduced rats served as controls. The early phase of ANG II-dependent hypertension was induced by five-days (5d) dietary indole-3-carbinol administration. Cardiac hypertrophy, ANG II and ANG 1-7 levels, protein expression of their receptors and enzymes were determined. Separate groups were subjected to acute myocardial ischemia/reperfusion injury, and infarct size and ventricular arrhythmias were assessed. Induced rats developed marked cardiac hypertrophy accompanied by elevated ANG levels. Ischemia/reperfusion mortality was significantly higher in induced than noninduced rats (52.1 and 25%, respectively). The blockade of AT1 receptors with losartan significantly increased survival rate in both groups. Myocardial infarct size was significantly reduced after 5d induction (by 11%), without changes after losartan treatment. In conclusion, we confirmed improved cardiac tolerance to ischemia/reperfusion injury in hypertensive hypertrophied rats and found that activation of AT1 receptors by locally produced ANG II in the heart was not the mechanism underlying infarct size reduction.